Privacy engineering for protection of personal identifiable information - Abdul Aziz, Normaziah; Hazrudden, Hareez Ishraf; Zulkifli, Abdul Haziq (IEEE, 2024)
The usage of data driven systems requires a serious concern on how users’ data privacy or specifically their Personal Identifiable Information (PII) are being handled. Privacy Engineering (PE) discipline needs to be cultivated among Computing students and software developers. Presently, data privacy discussion in Security courses and Software houses emphasis the enforcement of complying to data privacy legal acts. The technological aspects represented by PE, among others involve Privacy by Design (PbD) and Privacy Control Assessment tools are seldom taught. Thus, there is a gap between Privacy Engineering and Software Engineering, particularly in Malaysia. This work aims to give initial exposure to undergraduate students’ understanding and implementing privacy engineering in software development. A prototype of a mobile application is developed to demonstrate basic implementation of deidentification as part of PE, for an application that holds users’ PII.